(untitled) ("Journal "U". Economy. Management. Finance.", 2017)
The article considers a mechanism of the choice of strategy of corporate website promotion on the Internet. The authors suggest the methods to improve efficiency of the designed website and as a result to increase the number of visitors and sales volumes.